KENABIAN: PRESPEKTIF FILSAFAT ISLAM - Noor, Fauz (Siyasyatuna | Jurnal Hukum Tata Negara, 2024)
In the doctrine of faith in Islam, faith in the Holy Scriptures and faith in the Prophets are known. The philosophical value of these two doctrines, because humans after "finding" God in their contemplation, humans need a way to be able to relate to Him, that's why God also - with His Rahman Rahim nature - revealed the Holy Scriptures. Not only that, God also "chose" human beings who have special abilities (Al-Hads in the language of Ibn Sina) to convey His guidance as well as provide a good example for all mankind. There are some people who reject prophethood, such as Ibn Ruwandi, Abu Bakr Ar-Razi and Ibn Hayyan, on the grounds that prophethood is irrational. However, we cannot listen to their argument of "how to relate to God". Even if they explain how to relate to Him, they are acting as prophets. And if they act as prophets, they must be morally tested in the sense that they must be able to set a good example.